COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF CROSS-VILLAGE ROAD INFRASTRUCTURE IN KARANG REJO VILLAGE, SIMALUNGUN DISTRICT, GUNUNG MALIGAS DISTRICT - Bella Pertiwi (Universitas 17 Agustus 1945 Surabaya, 2023)
Karang Rejo is one of the villages in Simalungun district, Gunung Maligas sub-district, North Sumatra province, Indonesia. One of the things that is being focused on in the village is the road across the village which is increasingly deteriorating and dangerous for local people to pass through. Community participation is also very much needed to support the improvement of cross-village road infrastructure so that it is suitable for passage again and it is easy for people to carry out activities such as work, school, and other activities. Not only participation in decision making, but the community must also participate in implementing development. The purpose of this writing is to find out and analyze the role or participation of the community in the construction of cross-village roads in Karang Rejo village, Simalungun district. The author uses a method, namely a qualitative descriptive method where the author describes and analyzes the phenomena that occur in the problem. The results of this research are that there are still minimal people participating in the construction of cross-village road infrastructure in Karang Rejo village, Simalungun Regency, Gunung Maligas District. In the implementation of this development, those who are seen and participate are the people who give their energy and time rather than the people who donate materials and funds in the form of money. The government programs implemented are none other than for the community, so they require community involvement. The community needs to work together with the government to strengthen, facilitate, and maintain the implementation of development programs.